(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2023)
The research included the isolation of 12 bacterial isolates from stool samples of children with acute watery and bloody diarrhea under the age of five years, as it was possible to obtain 6 isolates of Escherichia coli, 3 isolates of Salmonella typhimurium, and 3 isolates of Shigella flexneri. Vitek2 system, and the inhibitory activity of lactoferrin and killer toxin produced from S. cerevisiae against pathogenic bacteria was studied by the well diffusion method, as the results recorded that the killer toxin had the highest inhibitory activity towards pathological bacteria with varying results, and the lowest inhibitory concentration was determined The MIC of the lactoferrin and the killer toxin against the bacterial isolates under study using the turbidity method in the tubes. for antibiotics, as the results showed a The relationship was synergistic due to the activity of lactoferrin with killer toxin in inhibiting the action of pathogenic bacteria, whose inhibitory activity increases with increasing concentration used.